Incidence and maternal-fetal risk factors of stillbirth. A population-based historical cohort and a nested casecontrol study - Maleki, Z.; Ghaem, H.; Seif, M.; Foruhari, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. For parents, stillbirth is a tragic experience; thus, identifying the associated risk factors can be beneficial in order to prevent this event. This study aimed to investigate the incidence and risk factors associated with stillbirth.Methods. In this historical cohort study, a total of 18,129 birth records were investigated. The outcome variable was having or not having stillbirth. For each case of stillbirth, three live birth infants on the same day and same hospital were selected as controls, which were matched for gestational age. The data were collected using a researcher-made checklist. Finally, data were analyzed using STATA, 13.0 with Cox proportional hazards regression model at the significance level of 0.05.Results. The cumulative incidence of stillbirth was 9.48 per 1,000 live births. Based on multivariate Cox regression model, five risk factors for stillbirth were identified, including male gender, fetal diseases, gestational hypertension, gestational diabetes, and maternal hypothyroidism, (all hazard ratios > 1 and p